Dukungan Sosial Selama Nifas Komplementer - Okta Zenita Siti Fatimah; Seventina Nurul Hidayah; Nora Rahmanindar (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
This research is a qualitative study aimed at exploring the experiences of mothers undergoing complementary postpartum period in the village of Bandasari, with a focus on the social support they receive during this period. Data were collected through in-depth interviews with mothers who had recently given birth and through participatory observation in the village. The results of this study indicate that social support plays a significant role in helping mothers cope with the physical and psychological challenges during the complementary postpartum period. This support comes from family, neighbors, and local community members. Furthermore, culture and local values also influence the types of support available and received by mothers. This study provides important insights into the significance of social support in maternal recovery after childbirth and underscores the crucial role of the community in providing support during the complementary postpartum period. Keywords: Social Support, Complementary Postpartum Period, Experiences